Association Between Urban Greenspace and Mental Wellbeing During the COVID-19 Pandemic in a U.S. Cohort - Wortzel, Jeremy D.; Wiebe, Douglas J.; DiDomenico, Grace E.; Visoki, Elina; South, Eugena; Tam, Vicky; Greenberg, David M.; Brown, Lily A.; Gur, Ruben C.; Gur, Raquel E.; Barzilay, Ran (Frontiers in Sustainable Cities, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic brought unprecedented socially isolating measures to mitigate the spread of disease, heightening the importance of public outdoor urban greenspace. Here, we investigated the association between tree-rich greenspace and mental health in a large opportunity sample surveyed using a crowdsourcing research website (www.covid19resilience.org) between April 6th and October 12th, 2020 during the pandemic in the United States. Participants living in the U.S. (N = 2,089, 83.1% females, mean age 42 years, age range 18–90 years) were mapped to 1,080 unique ZIP Codes and mean tree canopy density was calculated with a 250 m buffer around each ZIP Code grouped by quartile as a proxy for nearby greenspace. Four mental health parameters were assessed: (1) COVID-19-related worries; (2) anxiety symptoms; (3) depression symptoms; and (4) a standardized and weighted composite mental health score of all three parameters. Multivariate regression analyses with multilevel models were used to study the association between nearby greenspace and the four mental health outcomes, controlling for participant demographics and ZIP Code urbanicity. In the entire cohort, increased nearby greenspace showed a significant protective effect for depression (Coef. = −0.27; p = 0.0499), and composite mental health scores (Coef. = −0.19; p = 0.038) when comparing ZIP Codes with the most greenspace to ZIP Codes with the least, with no observed effects on COVID-19 related worries or anxiety individually. Stratifying by age suggested protective trends of greenspace on mental health in older subsets of the population (top age quartile, over 51 years old) experiencing less depression (Coef. = −0.45; p = 0.048) and lower composite mental health scores (Coef. = −0.34; – = 0.032) as a function of nearby greenspace. Additionally, younger subsets of the population (second youngest age quartile, 31–38 years) experienced lower COVID-19 related worries (Coef. = −1.34; p = 0.022) as a function of greenspace. These findings may indicate that tree-rich greenspace plays a protective role on mental health during the COVID-19 pandemic, specifically in certain age groups, supporting the use of greenspace-related strategies to help mitigate mental health burden during this challenging and isolating time.